A systematic review of patient satisfaction on health information exchange in Malaysian Public Healthcare Organizations - Ismail, Nurul Izzatty; Abdullah, Nor Hazana (IOP Publishing, 2018)
Patient satisfaction is imperative in every healthcare organization. Service quality is the utmost important aspect that yields patient satisfaction in hospitals. Since Information Technology (IT) is widely used in hospitals, its applications can give rise to different issues related to patient satisfaction. This is because patient satisfaction derived from utilizing health information exchange systems (HIEs) depends on the service quality of the systems. This paper presents a systematic review of the impacts of service quality of Health Information Exchanges (HIEs) on patient satisfaction. Five databases, namely Scopus, IEEE, Proquest, Emerald and Science Direct were accessed to search for relevant studies. In total, 714 studies met the inclusion criteria. The result shows that five factors at the healthcare organizations that adopted HIEs have impacts on patient satisfaction: Tangibility, Reliability, Assistance, Safety and Empathy.